Kajian UMKM Naik Kelas di Kabupaten Sleman Tahun 2020 - Suryanto, Rudy; Junaidi, Junaidi (Penerbit Goodwood, 2022)
Purpose: This study reveals the condition of MSMEs in the Sleman Regency area and how efforts must be made so that MSMEs are promoted. Research methodology: Qualitative approach with interviews and focus group discussions. Results: Based on the studies conducted, it is shown that the journey of MSMEs to advance to class is not an easy thing. At the pilot stage, SMEs must pass through what is called the